2021
DOI: 10.3390/nano11112799
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bioinspired Lithium-Doped Titanium Implants on Gingival Fibroblast Bioactivity and Biofilm Adhesion

Abstract: Soft tissue integration (STI) at the transmucosal level around dental implants is crucial for the long-term success of dental implants. Surface modification of titanium dental implants could be an effective way to enhance peri-implant STI. The present study aimed to investigate the effect of bioinspired lithium (Li)-doped Ti surface on the behaviour of human gingival fibroblasts (HGFs) and oral biofilm in vitro. HGFs were cultured on various Ti surfaces—Li-doped Ti (Li_Ti), NaOH_Ti and micro-rough Ti (Control_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 63 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Various materials and their different surface treatments have been extensively studied in vitro to assess their effects on peri-implant soft tissues, focusing on the fibroblast’s activity modulation and on the oral biofilm formation [ 15 , 16 , 17 , 18 , 19 ]. For example, a surface treated with nanoporous titanium dioxide (TiO 2 ) may change the reactivity of the implant surface; in fact, results from animal studies showed a decreased inflammatory reaction, a good epithelial attachment, and less marginal bone loss when compared to non-treated implants [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various materials and their different surface treatments have been extensively studied in vitro to assess their effects on peri-implant soft tissues, focusing on the fibroblast’s activity modulation and on the oral biofilm formation [ 15 , 16 , 17 , 18 , 19 ]. For example, a surface treated with nanoporous titanium dioxide (TiO 2 ) may change the reactivity of the implant surface; in fact, results from animal studies showed a decreased inflammatory reaction, a good epithelial attachment, and less marginal bone loss when compared to non-treated implants [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%